Identification of Complex Production Systems with Using Iterative Networks - A.M, Korneev; L.S, Abdullakh; A.B, Sukhanov; ., Antar; D, S; Kh.M, Al-jonid (International Journal of Engineering and Technology, 2018)
In the article the technique of identification of complex production systems using iterative networks is considered. The identification process begins with the allocation of functional blocks, which can later be described by automata working with discrete information and changing internal states only at specified times. The basic laws of the functioning of the selected subsystems are simulated. Characteristics of cells formed parameters associated with multi-step manufacturing process. As the semi-finished product passes through the processing stages under consideration, the values of the technological factors being realized are fixed in the system being formed.Â Â